Assessing the environmental impact of tofu production: a systematic review for a sustainable industry - Vioni Derosya; Taufiq Ihsan (AGROINTEK, 2025)
The tofu industry provides communities with affordable protein sources. As protein sources, the environmental impact of tofu production was compared to other protein sources. Further, the tofu industry also produces waste and by-products affecting the environment. Some previous studies learned the environmental impact of tofu production. In this study, we aim to get information on which stages of the process in the tofu industry impact the environment and what type of strategy is applied to reduce the environmental impacts. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) approach was then chosen to filter the most recent research publications published in international peer-reviewed journals. We found that most articles calculated the environmental impact based on GHG, which contributed mainly from imported soybeans and electricity used during production. This research can act as a foundation for further studies related to the tofu industries, enabling treatment, better strategies, and solutions for waste to be developed.